IDENTIFIKASI JENIS PEMBOROSAN YANG TERJADI PADA PT.PQR DENGAN MENGGUNAKAN METODE 8 WASTE - Tifani Bella Febrianty; Faizal Aziz Hermansyah; Ifham Azizi Surya Syafiin; Muchammad Fauzi (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2022)
Indonesia is a country whose industrial development is very rapid, this spurs industrial companies to continue to compete and make restorations in increasing their performance. An effective and efficient production system will form a quality and competitive product, as a result of which the company can obtain aporisma profit and avoid losses. The losses experienced by the company are caused by waste. PT. XYZ is one example of several Indonesian cigarette manufacturers that have been known by many people. This company often experiences conflicts that exist because of the permborosan. as an example of waste that occurs, namely the delay which is not uncommon in the production process. the emergence of the conflict was material for researchers to conduct research using one of the lean manufacturing tools "8waste". The purpose of this study is to analyze how the conflict occurs and what solutions must be done to carry out restoration so that the dilemma does not occur again in the coming year